2008
DOI: 10.1063/1.2896640
|View full text |Cite
|
Sign up to set email alerts
|

Superior characteristics of organic chalcone single crystals as efficient nonlinear optical material

Abstract: High-quality biaxial single crystals of chalcone derivatives were grown by solution growth technique. Their molecular structures were designed to possess large second-order nonlinearities by choosing proper donor/acceptor groups while retaining a high transparency in the visible and infrared spectral regions. The second-order nonlinear optical coefficients, determined by applying the Maker fringe technique, were found to be much larger than those of LiB3O5, KTiOPO4, KH2PO4, and urea. The advantages, such as ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The damage on the crystal could be due to the heating effect caused by linear absorption, and consequently the lower damage threshold at 532 nm could be due to higher linear absorption in the crystal. The laser damage threshold of PDBA was much higher than those of well-known potassium titanyl phosphate (KTP; 42, 4 GW/cm 2 at 1064 nm and 42 GW/cm 2 at 532 nm), potassium dihydrogen phosphate (KDP; 40.25 GW/cm 2 at 1064 nm and 48 GW/cm 2 at 532 nm [21] and other organic crystals, such as CDBA [19] and urea [31].…”
Section: Laser Damage Resistancementioning
confidence: 96%
See 1 more Smart Citation
“…The damage on the crystal could be due to the heating effect caused by linear absorption, and consequently the lower damage threshold at 532 nm could be due to higher linear absorption in the crystal. The laser damage threshold of PDBA was much higher than those of well-known potassium titanyl phosphate (KTP; 42, 4 GW/cm 2 at 1064 nm and 42 GW/cm 2 at 532 nm), potassium dihydrogen phosphate (KDP; 40.25 GW/cm 2 at 1064 nm and 48 GW/cm 2 at 532 nm [21] and other organic crystals, such as CDBA [19] and urea [31].…”
Section: Laser Damage Resistancementioning
confidence: 96%
“…The d-coefficients of PDBA crystal were determined using Maker fringe technique and the details of the measurement are presented elsewhere [21]. As-grown single crystals of PDBA having good surface quality and flatness allowed us to determine the second-order NLO d-coefficients.…”
Section: Nonlinear Optical Studiesmentioning
confidence: 99%
“…Chalcones are interesting organic NLO materials that show good crystallizability, high SHG conversion efficiency compared to urea and transparency extending down to the blue region [8][9][10][11][12][13][14]. From the past investigations on these molecules it was shown that these molecules show a higher SHG response when a p-electron acceptor group is substituted at the para position of the benzoyl group rather than at the phenylene group.…”
Section: Introductionmentioning
confidence: 97%
“…The substitution of electron acceptors/donors on either of the phenyl rings of chalcones greatly influences the noncentrosymmetric crystal packing structures required for second harmonic generation (SHG) [8]. It was suggested by Zhao et al [9] that electron donors such as -OCH 3 , -CH 3 , -Cl and -Br are the best donor groups for enhancing SHG in chalcones.…”
Section: Introductionmentioning
confidence: 98%
“…Chalcones are a class of cross conjugated NLO chromophores that exhibit high SHG efficiency, good crystallizability and excellent blue light transmittance [7,8]. The substitution of electron acceptors/donors on either of the phenyl rings of chalcones greatly influences the noncentrosymmetric crystal packing structures required for second harmonic generation (SHG) [8].…”
Section: Introductionmentioning
confidence: 99%